Ensino superior em Alagoas: a formação pedagógica na profissionalização docente - Oliveira, Renilda Correia de (2012)
This work is inserted in the research line History and Politics of Education Graduate Programat Federal University of Alagoas and the proposal was to critically analyze the profile of professionals who work as teachers in higher education institutions of the private sphere in Maceió, AL, trying to verify the existence of a formation that characterizes this group of professionals such as teachers, and where this training happens. We chose a descriptive qualitative approach, being the study developed through an intensive direct observation, using as a technique the interview. Were selected and interviewed in two private institutions of higher education located in the city of Maceió, AL, a total of 13 working in the teaching function in these institutions. We tried to consider, throught the light of the reflections developed by Masetto, Anastasiou and Pimenta, Zabalza, among others, the process of teacher training and perception about the meaning of pedagogical training for the practice of teaching in higher education. The analyzed data showed that the knowledge derived from training to the magisterium, as well as a locus for this training to happen is the gap of these professionals formation, in this way characterizing a process of professionalization still in progress. And that would constitute, in a cohesive and coherent, a group of professionals with characteristics of being a teacher, this gap needs to be filled.